Pengaruh Ukuran Perusahaan Dan leverage terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - helmi herawati (Universitas Prof.Hazairin,SH Bengkulu, 2021)
Effect of Company Size and Leverage Against Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange This study aims to determine the effect of company size and leverage on tax avoidance on manufacturing companies listed on the Indonesia Stock Exchange. The study was conducted on 18 manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2016-2018. The data analysis method uses multiple linear regression, with variables X1 (company size), X2 (leverage), against tax avoidance (Y).The results showed the multiple linear regression equation can be seen that X1 (company size) has a negative effect while X2 (leverage) has a positive effect on tax avoidance (Y), with the results of the regression test: Y = 0.211-0.200X1 + 0.109 X2 + e. The coefficient of determination obtained by 0.274. This means that X1 (company size) and X2 (leverage) affect tax avoidance (Y) by 27.4% while the rest (100% - 27.4% = 72.6%) is influenced by other variables that are not examined in this study. Based on the results of testing with the t test, testing for variable X1 (company size) shows a significance value of 0.002 <0.05, meaning X1 (company size) has a significant effect on tax avoidance (Y) on manufacturing companies listed on the Indonesia Stock Exchange . Variable X2 (leverage) shows a significance value of 0.021 <0.05. Because the significance value is less than 0.05, meaning X2 (leverage) does not have a significant effect on tax avoidance (Y) on manufacturing companies listed on the Indonesia Stock Exchange. Based on the results of testing the hypothesis with the F test, the results of statistical calculations show a significance value of 0.002 <0.05. This means that together X1 (company size) and X2 (leverage) have a significant effect on tax avoidance (Y)